Virtual Joint Field Campaign: a framework of synthetic landscapes to assess multiscale measurement methods of water storage - T. Francke; C. Brogi; A. Duarte Rocha; M. Förster; M. Heistermann; M. Köhli; D. Rasche; M. Reich; P. Schattan; P. Schattan; L. Scheiffele; M. Schrön (Geoscientific Model Development)
Various methods are available to measure water storage across different landscape compartments, e.g. cosmic-ray neutron sensing, remote sensing, or hydrogravimetry. All these methods provide integral estimates that are representative of their corresponding measurement volume.